Pencucian Membran Ultrafiltrasi Menggunakan Bahan Kimia NaOH Dan Surfaktan 5512 Pada Proses Penyaringan Air Terproduksi - Ritonga, Desrinayanti; Daud, Syarfi; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Water produced is the result of processing of petroleum that were uplifted to the surface with oil and gas, whose number is greather than the generated oil content. Produced water that goes in to a body of water without going through the very first processing has the potential to cause pollution of the environment. One of the technologies that are to manipulate the water produced using technology such as membrane. The toughest challenge in membrane technology is the fouling. This research to study the transmembrane pressure against flux, determine the effectiveness and efficiency of the concentration of NaOH and Surfactant chemistry wash of flux recovery and resistance removal in the process of ultrafiltrasi membrane technology in water filtration process produced and to get clean water from a water filtration process results produced using ultrafiltrasi membrane. The experiment was conducted using ultrafiltration membranes by feeding produced water. The method used is cross flow system by varying the operating pressure of 0,2, 0,4, and 0,6 bar, variations in the concentration of NaOH and Surfactant 1,5%, 2,0%, and 2,5%. Filtration process of produced water lasted for 180 minutes and each leaching time is 30 minutes, the highest effectiveness rate of 60,65% obtained by using surfactant 2,5%, the highest leaching efficiency based on flux recovery value is 98,87% and 60,66% for removal resistance. The highest flux value after chemical cleaning leaching obtained 1,501 ml/menit. in transmembrane pressure of 0,6 bar and the concentration of the surfactant, Where is the longer permeat through the membran with pressure so the smaller the resulting flux.Keywords: produced water; cross flow; flux recovery; membrane ultrafiltrasi; resistance removal